PEMANFAATAN TEKNOLOGI AUGMENTED REALITY UNTUK MEDIA PEMBELAJARAN PENGENALAN OBJEK GEOMETRI BERBASIS WEB - Setia Wardani; Marti Widya Sari (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2016)
The purpose of this study is to create a web-based learning media by using Augmented Reality (AR) Technology for object recognition Geometry and designing Geometry catalogs. The method used is the Microsoft Solution Framework (MSF) with a waterfall system development methods and the effectiveness of learning media is blackbox test and Alphatest. The conclusion after conducting research that Augmented Reality can display an object geometry either flat or wake up wake up the space into a simple three-dimensional shape that can be seen as a whole and can be used effectively in teaching.